Motion analysis in a swimming flume - Yang, H.; Fan, N. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction Motion analysis is one of the most important tools to objectively examine swimming technique. The conclusions drawn from such an analysis make it possible to improve individual swimming technique of swimmers for each specific event. A number of studies have reported that observations and measurements taken in a swimming flume are very helpful to motion analysis [1,2,3]. Methods A `three threads measuring system` was used to obtain measurements from subjects in the swimming flume. When swimming in a prone position the loop which fastens the "three-threads-measuringsystem" must be in the middle of the swimmer`s back and when swimming in a supine position it must be at the subjects navel area [1]. The principle of the measurement is based on the assumption that during a swimming cycle the impulses resulting from strokes and kicks, as well as the phases without impulse, cause alterations to the speed at the point of the hip. In order to record the inner-cyclic deviations, the changing position of the hip is measured by a three-threads-measuring-system [2]. Video records were obtained which are related to the speed curves. These provide the necessary precision to interpret the curves of the measured parameters in order to reveal any cause-effect relationships. The causal correlations between impulse, resistance, velocity range, coordination, body position in the water and breathing can be clearly demonstrated. Results / Discussion The speed curves can be recorded in all three space co-ordinates (Y - with and against the swimming direction; X - horizontally perpendicular to the swimming direction; Z - vertically perpendicular to the swimming direction). For swimmers whom have already achieved good-quality technique, this proves to be of great importance in order to reveal their individual reserves. The process requires a sizeable amount of work as well as efficient biomechanicists and coaches with expertise in the swimming technique. In practical work it was proved to be sufficient to measure the Y - co-ordinate only, since it most obviously exposes the effects of both impulse and resistance. The inner-cyclic speed curve of a breast-stroke swimmer is given as an example. The ordinate value of the abscissa corresponds to the set velocity of the flume. For the analyses it proved to be sufficient to set the pace for each swimmer at the same as his/her pace (m/s) of their current best performance. However, In this case it does not matter whether the speed is 2.00 m/s or 1.35 m/s - the ordinate value is always 0. The components of the curve above the abscissa indicate velocities surpassing that of the flume, those below the abscissa indicate a braking effect. A breast-stroke swimmer is given as an example. In the stage of the stroke in which the legs are pulled under the buttocks, an evasive upward movement is created which leads to an extreme loss of speed. This loss can only be reduced by actively pushing the hip downward. To interpret the inner-cyclic V-t-curves we distinguish between the impulse, which is determined by the general and specific strength presuppositions and the precise structures of the technique, and the propulsion which results from the impulse and is decreased by the frontal, wave and friction resistance. Conclusions Use of the "three-threads-measuring-system" for motion analysis has been established to be a simple and valid way to identify swimming stroke imperfections, improve technique and minimize the resistance.